Incubator Temperature and Oxygen Concentrations During the Plateau Stage in Oxygen Uptake Affect Turkey Embryo Plasma T4 and T3 Concentrations - Christensen, V.L.; Wineland, M.J.; Yildirum, I.; Fairchild, B.D.; Ort, D.T.; Mann, K.M. (International Journal of Poultry Science, 2005)
Avian embryo thyroid responses to incubator temperature and oxygen concentrations during the plateau stage in oxygen consumption were measured. It was hypothesized that turkey embryo thyroid responds in a limited way at this critical time to environmental conditions to modulate basal metabolism. Turkey embryos were exposed to one of four incubator temperatures (36, 37, 38 or 39oC) beginning on the 25th day of incubation at the onset of the plateau, a time when plasma thyroxine (T4) and triiodothyronine (T3) concentrations normally increase. Blood was collected and thyroid hormone concentrations were measured at pipping (27th day) and hatching (28th day). Elevated temperatures depressed T3 and T4 concentrations and increased the T3 to T4 ratios. In a second experiment four oxygen concentrations (17, 19, 21 or 23% oxygen) were provided to the embryos using identical procedures. The 21% treatment significantly reduced T3 and T4 at pipping compared to all other treatments, but 23% oxygen increased plasma T3 and the T3 to T4 ratio compared to all other treatments. The 17% oxygen treatment elevated T3 compared to all other treatments. At hatching, 23% oxygen elevated T3 and T3 to T4 ratios compared to all other treatments. When temperature and oxygen treatments were applied together in a factorial arrangement, temperature and oxygen affected T3 and T4 hormone concentrations independently but did not interact. Therefore, we conclude that temperature and oxygen are independent stimuli of the avian embryonic thyroid gland during the plateau stage, and that incubator temperature and oxygen concentrations can modulate development of turkey embryos by changing plasma T3 and T4 concentrations.